Appropriate prevention of vitamin D deficiency in the population of the Irkutsk region - T. A. Spasich; L. A. Reshetnik; E. Y. Zhdanova; N. E. Chubarova; M. V. Promtov; K. S. Rumyantsev; B. V. Boskholov (Acta Biomedica Scientifica, 2017)
Purpose of the study. To determine the influence of climatic and geographical factors of the Irkutsk region on the risk of hypovitaminosis D in children and adults. Patients and methods. The contents of 25(OH)D-3 in the blood of children and adults (3261 samples) were evaluated. The materials were obtained in the Diagnostic Center of the region and the InVitro laboratory. Results of monitoring of ultraviolet radiation and precipitation in the Irkutsk region for 2014-2015 were analyzed according to ground and satellite measurements. Results. The Irkutsk region is in the zone of ultraviolet insufficiency during the period from September-October to March-May. The status of the metabolite of vitamin D - 25(oH)D3 in the population of the region is low, especially in adolescents and people older than 70 years. 68 % of children have vitamin D deficiency. Activity of 25(oH)D3 depends on meteorological factors, especially the level of precipitation and the intake of vitamin D. For each geographical area of the region, time intervals were calculated for the formation of vitamin D in the skin under the influence of ultraviolet radiation and time intervals for the intake of vitamin D preparations. The exposure time in the sun was calculated for the formation of vitamin D for individuals with different skin phototypes, depending on the degree of its openness.